Click chemistry-based core–shell molecularly imprinted polymers for the determination of pyrimethamine in fish and plasma samples. Issue 23 (5th June 2018) - Huang, Shuyi; Guo, Manli; Tan, Lei; Tan, Jiean; Wu, Jinyi; Tang, Youwen; Liang, Yong
Abstract : This paper demonstrates the development and validation of a high-performance liquid chromatography (HPLC) method for the determination of pyrimethamine in fish and plasma samples using core–shell molecularly imprinted polymers (MIPs). Abstract : This paper demonstrates the development and validation of a high-performance liquid chromatography (HPLC) method for the determination of pyrimethamine in fish and plasma samples using core–shell molecularly imprinted polymers (MIPs). The MIPs were synthesized based on thiol–ene click chemistry, using pentaerythritol tetra (3-mercaptopropionate) and dipentaerythritol pentaacrylate as binary cross-linkers, pyrimethamine as a template and methacrylic acid as a functional monomer. The MIPs were characterized by scanning electron microscopy (SEM) and Fourier transform infrared spectroscopy (FT-IR). The MIPs were used as matrix solid-phase dispersion extraction sorbents for the separation of pyrimethamine in fish and plasma samples. The results show that the developed MIPs had higher extraction capacity toward pyrimethamine than non-imprinted polymers (NIPs), high selectivity among pyrimethamine analogues, and a saturation capacity of 41.9 μmol g −1 . Furthermore, the proposed method was validated for linearity, precision, accuracy, and it has been applied for the analysis of pyrimethamine in fish and plasma samples, obtaining satisfactory recoveries.